Successful discontinuation after 7 years of hemodialysis following Toprak’s kidney care: A case report - Omer Toprak; Emel Aslan Bozyel; Didar Elif Akgun (Ukrainian Journal of Nephrology and Dialysis, 2023)
Patients with end-stage kidney disease, who require hemodialysis for more than three months, have little chance of terminating dialysis. The purpose of this case report is to show the effects of patient kidney care and nutrition on the termination of dialysis and patient follow-up. We present a 74-year-old end-stage kidney disease patient who underwent hemodialysis 3 times a week for 7 years. After the patient underwent a special kidney care and nutrition program called Toprak's Kidney Care, hemodialysis was terminated by gradually reducing the dialysis sessions over 2.5 months. During the 62-month follow-up after discontinuing dialysis, the patient required no kidney replacement therapy. The glomerular filtration rates were stable at 8-10 mL/min/1.73 m2. During the follow-up period, the patient was not hospitalized and no major adverse cardiac events occurred. To date, the patient remains in good health.Toprak’s Kidney Care and nutritional support may be considered during the termination of HD in ESKD patients. The discontinuation of HD in ESKD patients who have adequate urine output may be considered, even after 7 years of HD. Consensus and clinical guidelines regarding the termination of chronic HD in ESKD patients are needed